Improving the demand forecasting process in a Finnish food manufacturing company - Siren, Lotta (My University, 2020)
According to literature, demand forecasting is one of the most essential components for both strategic and tactical business planning. Forecasting is a general problem in businesses, since it is basically impossible to forecast the future accurately. However, almost every single business decision is related to the future, so they are all based on forecasts. This research was done as an assignment for a Finnish food manufacturing case company. The research problem was to examine and suggest improvements to their demand forecasting process in six different market areas. Based on literary review, the conceptual framework for demand forecasting was divided into five segments: internal integration and external integration, information types and information quality, forecast combinations and judgmental adjustments, forecast horizon and forecast frequency, forecasters and group forecasting techniques. The primary data for this research was gathered through semi-structured interviews of key personnel in the demand forecasting process of the case company. According to this qualitative research, external integration with many clients was insufficient and increase in information flow and quality is needed. Main problems found were that retailers give forecasters short horizon information while procurement needs long horizon information for manufacturing. Many times retailers did not give forecasts, they arrived too late to procurement or were incorrect, especially for novelty products. A remarkable point of improvement would be better communication externally and internally regarding demand forecasts. Based on literature, using more forecast combinations and group forecasting with clients could increase the forecast accuracy. More training, better IT tools, and frozen time frames, when forecasts for procurement cannot be altered anymore, were improvements suggested by the interviewees. Also, forecasting time horizons could be more in line within the organization.

Kirjallisuuden mukaan kysynnän ennustaminen on yksi tärkeimmistä komponenteista sekä strategisessa että taktisessa liiketoiminnan suunnittelussa. Ennustaminen on yleinen ongelma yrityksissä, koska tulevaisuutta on lähtökohtaisesti mahdotonta ennustaa tarkasti. Lähes jokainen liiketoimintapäätös liittyy kuitenkin tulevaisuuteen, joten ne kaikki perustuvat ennusteisiin. Tämä tutkimus tehtiin toimeksiantona suomalaiselle elintarvikevalmistusyritykselle. Tutkimusongelmana oli tutkia ja ehdottaa parannuksia kysynnän ennusteprosessiin kuudella eri markkina-alueella. Kirjallisuuskatsauksen perusteella kysynnän ennustamisen teoreettinen viitekehys jaettiin viiteen segmenttiin: sisäinen integraatio ja ulkoinen integraatio, informaatiotyypit ja informaation laatu, yhdistelmäennusteet ja arviointiin perustuvat tarkennukset, ennustehorisontti ja ennustetaajuus, ennustajat ja ryhmäennustustekniikat. Tämän tutkimuksen perustiedot kerättiin tapausyrityksen kysynnän ennustamisprosessin avainhenkilöiden puolistrukturoiduilla haastatteluilla. Tämän laadullisen tutkimuksen mukaan ulkoinen integraatio monien asiakkaiden kanssa oli riittämätöntä ja tiedonkulkua ja tiedon laatua tulisi pyrkiä lisäämään. Suurimmat havaitut ongelmat olivat, että vähittäiskauppiaat antoivat ennustajille lyhyen aikavälin tietoja, kun taas tuottajan hankinta tarvitsee pitkän aikavälin tietoja tuotantoa varten. Usein vähittäiskauppiaat eivät antaneet ennusteita, ennusteet saapuivat liian myöhään hankintaan tai olivat virheellisiä etenkin uutuustuotteiden osalta. Merkittävä parannuskohta olisi parempi kysynnänennusteisiin liittyvä viestintä ulkoisesti ja sisäisesti. Kirjallisuuden perusteella yhdistettyjen ennusteiden ja ryhmäennusteiden laajempi hyödyntäminen asiakkaiden kanssa voisi parantaa ennusteiden tarkkuutta. Lisää koulutusta, parempia IT-työkaluja ja jäädytetyt periodid, jolloin hankintaennusteita ei voida enää muuttaa, olivat haastatteluista esiin nousseita parannusehdotuksia. Myös ennustehorisontti voisi olla paremmin linjassa organisaation sisällä.
Keywords: demand forecasting, planning, procurement